(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Dental extractions are usually carried out in non-sterile environment using clean non-sterile gloves. However, the use of non-sterile gloves are frequently probed for post surgical socket healing complications. Hence it is necessary to gather clinical proofs to answer this query. The present study aimed to compare healing complications of dental extraction performed with and without sterile gloves. Methods: The study design was comparative cross-sectional. The sample size was calculated as 51 per group. The patients were randomly allocated to either group by allowing them to choose a lottery. All the patients undergoing non surgical dental extraction constituted the study population for present study. History taking and observation technique was used to collect data. The proforma was prepared and filled up by the researcher. Results: Four (7.8%) cases in clean sterile group and 3 (5.9%) cases in surgical gloves group had some complications. The difference in presence of complications across groups was not significant. Conclusion: The non-sterile clean gloves do not increase the incidence of postoperative complications as compared to sterile gloves.